Examining the Extent to which Elements of the Chronic Care Model Address Barriers to effective Self-Management of Patients with Multiple Chronic Conditions - Serugunda, Henry M.; Namatovu, Hasifah K.; Muwoge, Bernard S.; Kimbugwe, Nasser (Prague, 2022)
Multiple chronic conditions among patients is still a big public health burden across the globe, yet when properly managed, it can improve patient health outcomes. Despite the studies that have been conducted, little is known about the effectiveness of the chronic care model elements in addressing barriers to self-management of patients with multiple chronic conditions. Therefore, this study set out to study the effectiveness of the Chronic Care Model (CCM) in addressing self-management (SM) barriers of patients with multiple chronic conditions (MCC). A comprehensive literature search was conducted in PubMed, google, google scholar, ScienceDirect, Embase, Cochrane library for English studies published in between 2007 – 2021. Articles were included if they were peer reviewed and focused on barriers to self-management of patients with multiple chronic condition and chronic care model implementation. Data was synthesized, carefully mapped, categorised to eliminate ambiguity and thematized to increase clarity. From an initial population of 105 articles, 18 articles passed on grounds of relevance. Literature was classified into patient centred barriers, health provider barriers, and environmental barriers. This study revealed that the CCM does not address multimorbidity SM barriers of; limited resources, distance to health facilities, conflicting information, treatment burden and environmental barriers. Therefore there is need for a model applicable in low resource settings that addresses the identified gaps in the CCM for effective SM of patients with MCC. There is a need for policies that enable coordination and communication amongst public and private multiple chronic care providers. Chronic Care providers need to adopt a holistic approach in managing patients with MCC.
Keywords: Self-management (SM), Multiple Chronic Conditions (MCC), Multimobidity, Chronic Care Model